Queer Atlantic: masculinity, mobility, and the emergence of modernist form - Hannah, Daniel (McGill-Queen's University Press, 2021)
"How can we talk about analogies drawn by fiction between geographical, erotic, and formal mobility? What does it mean when a male character's movements resemble both a privileged kind of wandering and queerly suggestive cruising? Or when a male protagonist's sexual magnetism becomes a force for both social disorder and imperialist expansion? In this analysis of works by five British and American authors, Daniel Hannah examines how masculine mobility--and often specifically transatlantic mobility--both enacts and queerly disorients male privilege, even as that same mobility works as a kind of unstable master trope behind the restless experimentation of modernist fiction. Where the "new modernist studies" has sought to diversify the canon, Queer Atlantic addresses established writers (Melville, Stevenson, James, Conrad, and Ford), arguing for the significance of anxieties about white, masculine privilege and queer potential to their broadening of the novel's formal possibilities. Hannah places these writers in the context of their responses to debates about naval impressment, piracy, emigration, colonization, and the "new imperialism." In the process, he also raises significant questions about the current field of queer ethics, highlighting the strange companionship of queer openness to otherness and imperialist thought for modernist writing. Turning, in its final pages, to examine the surprising resilience of such fictional structures for a more diverse set of American writers after World War One, Queer Atlantic opens out a new understanding of modernism's emergence from a troubling of masculine privilege, mobility, and desire."--